Endoscopic Endonasal Surgical Strategy for Skull Base Chordomas Based on Tumor Growth Directions: Surgical Outcomes of 167 Patients During 3 Years - Bai, Jiwei; Li, Mingxuan; Xiong, Yujia; Shen, Yutao; Liu, Chunhui; Zhao, Peng; Cao, Lei; Gui, Songbai; Li, Chuzhong; Zhang, Yazhuo (Frontiers in Oncology, 2021)
Background: Skull base chordomas (SBCs) are rare malignant bone tumors with dismal long-term local control. Endoscopic endonasal surgeries (EESs) are increasingly adopted to resect SBCs recently. Gross total resection (GTR) favors good outcomes. However, the SBCs often invade the skull base extensively and hide behind vital neurovascular structures; the tumors were challenging to be removed entirely. To improve the GTR, we established a surgical strategy for EES according to the tumor growth directions. Methods: 112 patients with SBCs from 2018 to 2019 were classified into the derivation group. We retrospectively analyzed their radiologic images and operation videos to find the accurate tumor locations. By doing so, we confirmed the tumor growth directions and established a surgical strategy. Fifty-five patients who were operated on in 2020 were regarded as the validation group, and we performed their operations following the surgical strategy to verify its value. Results: In the derivation group, 78.6% of SBCs invade the dorsum sellae and posterior clinoid process region. 62.5% and 69.6% of tumors extend to the left and right posterior spaces of cavernous ICA, respectively. 59.8% and 61.6% of tumors extend to the left and right posterior spaces of paraclival and lacerum ICA (pc-la ICA), respectively. 30.4% and 28.6% of tumors extended along the left and right petroclival fissures that extend toward the jugular foramen, respectively. 30.4% of tumors involved the foramen magnum and craniocervical junction region. The GTR was achieved in 60.8% of patients with primary SBCs in the derivation group. Based on the tumors’ growth pattern, pituitary transposition and posterior clinoidectomy techniques were adopted to resect tumors that hid behind cavernous ICA. Paraclival ICA transposition was used when the tumor invaded the posterior spaces of pc-la ICA. Lacerum fibrocartilage resection and eustachian tube transposition may be warranted to resect the tumors that extended to the jugular foramen. GTR was achieved in 75.0% of patients with primary SBCs in the validation group. Conclusion: Besides the midline clival region, the SBCs frequently grow into the eight spaces mentioned above. The surgical strategy based on the growth pattern contributes to increasing the GTR rate.